Improvement of the statical behaviour of pressure controlled axial piston pumps - Lovrec, Darko (Strojniški vestnik, 2009)
The control of pressure by means of variable displacement pumps is one of the most important tasks in the field of pump control, which is influenced by the properties of the pumps. Looking for a suitable control concept with good static behaviour, a method is tested which tunes the parameters of a controller. Instancing a variable displacement axial piston pump controlled bya 3/2 proportional valve the improvement will be achieved by fuzzy logic on the one hand and a non-linear approach - adaptation of gain of the classical controller - on the other.
Keywords: hidravlika; batne črpalke; aksialne črpalke; tlak